Conservation Key points and management strategies of historic villages: 10 cases in the Guangzhou and Foshan Area, Guangdong Province, China - Yi Huang; Erwei Li; Dawei Xiao (Journal of Asian Architecture and Building Engineering, 2022)
Historic villages form a nonrenewable part of our cultural heritage that is being affected by changes in modern production methods and lifestyles. Historic villages require various conservation measures, and their performance requires post-planning evaluation. An evaluation system and its criteria for the conservation of historic villages has been established, and 10 historic villages in the Guangzhou and Foshan Area, Guangdong Province, China, have been used as examples to quantify the performance of their heritage conservation. Furthermore, the evaluation results are compared with the conservation measures to determine key points and strategies that facilitate improvement of conservation performance and to provide a technical reference for future conservation work.